2018
DOI: 10.7575/aiac.alls.v.9n.2p.17
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Video Technology on Improving Reading Comprehension of Iranian Intermediate EFL Learners

Abstract: With the development of educational technology, the concept of technology-enhanced multimedia instructions is using widely in the educational settings. Technology can be employed in teaching different skills such as listening, reading, speaking and writing. Among these skills, reading comprehension is the skill in which EFL learners have some problems to master. Regarding this issue, the present study aimed at investigating the effect of video materials on improving reading comprehension of Iranian intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 6 publications
2
25
0
Order By: Relevance
“…It can be used as media in teaching various skills such as listening, reading, speaking and writing. Among these skills, reading comprehension is a skill in which EFL students have several problems to master (Mohammadian, Amir|Saed, Amin|Shahi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It can be used as media in teaching various skills such as listening, reading, speaking and writing. Among these skills, reading comprehension is a skill in which EFL students have several problems to master (Mohammadian, Amir|Saed, Amin|Shahi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The English teacher is suggested to use this media in increasing students' reading ability. It is supported by the result of an experimental research by Saed, A., & Shahi, Y (2018), who said that the video material had effect on promoting reading comprehension of the Iranian students. Next, according to Semaan, C and Ismail, N ( 2018) who said that the implementation of Pawtoon has positive effects on the learners' comprehension and developing reading strategies.…”
Section: Conclusion and Suggestionmentioning
confidence: 82%
“…Lee & Liang, 2012). It is also not only used to learn speaking skills but also to learn reading skills (Mohammadian, Amir|Saed, Amin|Shahi, 2018). It is concluded that video helps the students easier in increasing their English skills.…”
Section: Introductionmentioning
confidence: 99%